Differentiated Engagement as a Model for Managing Marginal Colonial Industrial Heritage: A Case Study of Spoorlaan-Kemijen, Semarang - Albertus Kriswandhono; Fransçois Sémah; Titi Susilowati; Wilson MA Therik (Interdisciplinary Social Studies, 2026)
The preservation of cultural heritage in Indonesia's marginal urban areas faces complex challenges, particularly in the Spoorlaan-Kemijen area in Semarang. This study examines the paradoxical conditions of such sites, which are historically significant but suffer from physical degradation and lack formal protection. Using a mixed-methods sequential explanatory approach, the research identifies social fragmentation in local perceptions of heritage preservation and environmental concerns. Findings reveal a lack of correlation between environmental concerns and active conservation support, attributed to institutionalized dichotomies and tenure conflicts. The study introduces the Differentiated Engagement, Integrated Vision (DEIV) model, which offers a tailored governance approach for these sites. The model recognizes the diverse interests of three social clusters—Memory Keepers, Environmental Pragmatics, and Integrators—by creating a deliberative space for dialogue and cooperation. The research suggests that sustainable heritage preservation in marginalized areas requires a shift from awareness-raising to institutional transformation. This study contributes to theoretical discussions on heritage governance by reconceptualizing the ethical trilemma and provides practical solutions for marginalized heritage management. The DEIV model offers a replicable framework for other heritage sites in Indonesia, fostering inclusive participation and long-term sustainability in urban heritage preservation.